An ℓ2-consistent event-triggered control policy for linear systems. (March 2021) - Balaghiinaloo, Mohammadhadi; Antunes, Duarte J.; Heemels, W.P.M.H. (Maurice)
Abstract: In this article, we consider the design of an event-triggered ℓ 2 -control policy, for a setting where a scheduler is arbitrating state transmissions from the sensors to the controller of a discrete-time linear system. We start by introducing a periodic time-triggered ℓ 2 -controller for different transmission time-periods with a given ℓ 2 -gain bound using the minimax game-theoretical approach. After that, we propose an ℓ 2 -consistent event-triggered controller in the sense that it guarantees at least the same ℓ 2 -gain bound as the designed periodic time-triggered ℓ 2 -controller, however with a larger, or at most equal, average inter-transmission time. In practice, for typical disturbances, the proposed event-triggered scheme can lead to significant gains, both in terms of communication savings and disturbance attenuation, compared to periodic time-triggered policies, which is illustrated through a numerical example.